2003
DOI: 10.1177/107754603031169
|View full text |Cite
|
Sign up to set email alerts
|

Structural Damping and Vibration Control via Smart Sensors and Actuators

Abstract: Public Reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of infomiation. Send comment regarding this burden estimates or any other aspect of this collection of information, including suggestions for reducing tfiis burden, to Washington Headquarters Services, Directorate for information Operations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Structural control is classified into active and passive control systems. In general, active control by sensors and actuators automatically provides the structure with a response against disturbance (Garg and Anderson, 2003). Passive control dissipates only a part of the energy when associated with spoilers or dampers (Modi and Seto, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Structural control is classified into active and passive control systems. In general, active control by sensors and actuators automatically provides the structure with a response against disturbance (Garg and Anderson, 2003). Passive control dissipates only a part of the energy when associated with spoilers or dampers (Modi and Seto, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrations caused by the thermal effect and external excitation are also modeled as displacement or moment boundary conditions. The contribution of material damping to the piezoelectric control of a system without time delay in control function has been studied in the [8] and it was observed that neglecting natural damping leads to under-estimation of the structural behavior [12].…”
Section: Introductionmentioning
confidence: 99%
“…Airframe systems such as landing gear control and indication, and control surface position require various sensors for monitoring and control of airframe systems. The nonlinear vibration suppression technique was robust and efficient and it functioned with most sensors and actuators (Garg and Anderson, 2003). The size and location of the piezoelectric actuators are two issues to guarantee the highest energy efficiency and controllability of the system (Fariborzi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%